2009
DOI: 10.1098/rspb.2009.1605
|View full text |Cite
|
Sign up to set email alerts
|

The role of population heterogeneity and human mobility in the spread of pandemic influenza

Abstract: Little is known on how different levels of population heterogeneity and different patterns of human mobility affect the course of pandemic influenza in terms of timing and impact. By employing a large-scale spatially explicit individual-based model, founded on a highly detailed model of the European populations and on a careful analysis of air and railway transportation data, we provide quantitative measures of the influence of such factors at the European scale. Our results show that Europe has to be prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
244
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(258 citation statements)
references
References 23 publications
8
244
1
5
Order By: Relevance
“…Another important feature that is needed to decipher the impact of demographic transition and immunization programmes, but that is missing in this model, is the spatial structure. Accounting for differences in population density [10] and patterns of human mobility [33][34][35] could help to explain large regional differences in terms of case incidence and average age at infection. However, retrieving longitudinal/historical mobility data to determine the strength of the connections between spatially distinct populations is a very hard task.…”
Section: Resultsmentioning
confidence: 99%
“…Another important feature that is needed to decipher the impact of demographic transition and immunization programmes, but that is missing in this model, is the spatial structure. Accounting for differences in population density [10] and patterns of human mobility [33][34][35] could help to explain large regional differences in terms of case incidence and average age at infection. However, retrieving longitudinal/historical mobility data to determine the strength of the connections between spatially distinct populations is a very hard task.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that cities with different mobility patterns may also differ in the rate at which their inhabitants have infectious contact, leading to variation among cities in the risk of an epidemic [5][6][7]. Human movement patterns are heterogeneous at a wide range of scales-from within a building [8] to among countries [9][10][11], as evidenced by diverse sources of data, including the movements of mobile phone users [12,13], air travel patterns [9][10][11] and census data on commuting patterns [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Individual variation in rates of infectious contact can significantly alter patterns of disease spread [6,7,15,[19][20][21] and theoretical models of disease dynamics within and among cities (both individual-based simulations [5,7,10,15,[22][23][24] and metapopulation models [10,11,14,15,[25][26][27]) have shown that heterogeneous contact patterns are potentially important in determining urban epidemic dynamics. However, few studies have examined whether empirical variation in intracity mobility patterns is sufficient to drive detectable differences in epidemic dynamics among cities.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the complete cycle of influenza infection and defines the incubation period. In general, because influenza viruses are transmitted through air, speaking, coughing or sneezing, once a person is infected, the incubation period is short, approximately 1-3 days [19][20][21][22][23]. The onset of clinical symptoms can also be after approximately 7 days.…”
Section: Influenza Investigationmentioning
confidence: 99%